1997
DOI: 10.1095/biolreprod57.4.756
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Differentiation of Porcine Inner Cell Mass and Epiblast in Vitro1

Abstract: The proliferation rate and differentiation state were investigated in porcine inner cell masses (ICMs) and epiblasts in vitro. ICMs isolated from early blastocysts (Day 7 of pregnancy) and epiblasts isolated from preelongated blastocysts (Day 11 of pregnancy) were cultured for up to 5 days in the presence of human leukemia inhibitory factor (hLIF) (1000 U/ml). The proliferation rate was evaluated by determination of the percentage of cells in S-phase. The differentiation state was determined by studying the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…This observation correlates with observations in mEpiSC that show no AP activity [ 6 ]. Surface marker expression shows that mEpiSC are SSEA-1-positive [ 6 , 19 ] and similar observations were reported for pig epiblasts [ 20 ]. We detected strong SSEA-1 expression in cultured epiblasts and weak or no expression of SSEA-4 ( Fig.…”
Section: Epiblast Isolation Stem Cell Cultures and In Vitro Differesupporting
confidence: 92%
See 2 more Smart Citations
“…This observation correlates with observations in mEpiSC that show no AP activity [ 6 ]. Surface marker expression shows that mEpiSC are SSEA-1-positive [ 6 , 19 ] and similar observations were reported for pig epiblasts [ 20 ]. We detected strong SSEA-1 expression in cultured epiblasts and weak or no expression of SSEA-4 ( Fig.…”
Section: Epiblast Isolation Stem Cell Cultures and In Vitro Differesupporting
confidence: 92%
“…We show that pEpiSC can reactivate the specifi c germ cell markers DAZL and VASA after induction with BMP-4. The capacity of BMP-4 to induce germ cells has been shown in vivo in the mouse [ 40 ] and in vitro with hESC [ 20 ]. Thus, our results with pEpiSC show that the role of BMP-4 as an inducer of the germ cell lineage is conserved.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly, cortical microfilament bundles running between apical junctional complexes are present in the epiblast cells of the chicken primitivestreak-stage blastoderm, a stage where gastrulation is rapidly ensuing (Vakaet and Vanroelen, 1982). Also, a study of differentiation markers showed an undifferentiated state of freshly isolated pig epiblasts taken from 7-and 11-day embryos, and then the differentiation of the epiblast cells within only a few days of culture (Wianny et al, 1997). Thus, it is possible that the appearance of microfilament bundles, cortical and perinuclear, within the cultured pig epiblast cells are differentiation events.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has also been successfully used in the pig [6,20,21,23,28,29,37,38]. Wianny et al [25] developed another immunosurgical method when using a monoclonal antibody SN1/38 specifically raised against porcine trophectodermal cells [50]. Other methods used include treatment with calcium ionophore [51], microsurgery [22,24,32,48] and a digestive method using 0.25% Trypsin/EDTA [30,31].…”
Section: Icm Isolationmentioning
confidence: 99%